Using OAI-ORE to transform digital repositories into interoperable storage and services applications - Tarrant, D; O’Steen, B; Brody, T; Hitchcock, S; Jefferies, N; Carr, L (Code4Lib, 2009)
In the digital age libraries are required to manage large numbers of diverse objects. One advantage of digital objects over fixed physical objects is the flexibility of ‘binding’ them into publications or other useful aggregated intellectual entities while retaining the ability to reuse them independently in other contexts. An emerging framework for managing flexible aggregations of digital objects is provided by the Open Archives Initiative (OAI) with its work on Object Reuse and Exchange (ORE). This paper will show how OAI-ORE is being used to manage content in digital repositories, in particular institutional repositories, and has the potential ultimately to transform the conception of digital repositories.